Implementation of project-based learning in developing a human anatomy and physiology practical guidebook with analysis of the nutritional content of local NTT ingredients - Florentina Yasinta Sepe; Maria Novita Inya Buku; Vinsensia H. B. Hayon; Hildegardis Missa; Getrudis Wilhelmina Nau; Aloysius Djalo (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Practical learning that is relevant to local potential is needed so that students understand human physiology concepts theoretically and are able to relate them to real life. This can support the improvement of 21st century skills while also supporting the utilization of local resources in education and community empowerment. This study aims to develop a practical guidebook for the Human Anatomy and Physiology course based on Project-Based Learning (PJBL) with the integration of nutritional content analysis of local food ingredients from East Nusa Tenggara (NTT). The problem faced is the limited availability of practical teaching materials that are relevant to local conditions, specifically linking anatomy and physiology topics with an understanding of the nutritional content of local food ingredients. The method used is research and development with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of the study show that the developed practical guidebook is relevant and effective in enhancing students' understanding of human anatomy and physiology concepts and the nutritional content of local food ingredients. Evaluation of the product indicates positive responses from students, with improvements in active involvement, critical thinking skills, and significant learning outcomes. This guidebook also helps students to better understand scientific concepts in the context of everyday life. In conclusion, the application of PJBL with a focus on local food ingredients from NTT proves to be effective in improving students' understanding and 21st-century skills.Abstrak. Pembelajaran praktikum yang relevan dengan potensi lokal dibutuhkan agar mahasiswa memahami konsep fisiologi manusia secara teoritis dan mampu mengaitkan dengan kehidupan nyata. Hal ini dapat mendukung peningkatan keterampilan abad ke-21 sekaligus mendukung pemanfaatan sumber daya lokal dalam pendidikan dan pemberdayaan masyarakat. Penelitian ini bertujuan untuk mengembangkan buku petunjuk praktikum mata kuliah Anatomi dan Fisiologi Manusia berbasis Project-Based Learning (PJBL) dengan integrasi analisis kandungan gizi bahan pangan lokal Nusa Tenggara Timur (NTT). Permasalahan yang dihadapi adalah terbatasnya ketersediaan bahan ajar praktikum yang relevan dengan kondisi lokal, khususnya yang mengaitkan topik anatomi dan fisiologi dengan pemahaman kandungan gizi bahan pangan lokal. Metode yang digunakan adalah penelitian dan pengembangan dengan model ADDIE, yang terdiri dari lima tahap yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Hasil penelitian menunjukkan bahwa buku penuntun praktikum yang dikembangkan relevan dan efektif untuk meningkatkan pemahaman mahasiswa terhadap konsep anatomi dan fisiologi manusia serta kandungan gizi bahan pangan lokal. Evaluasi terhadap produk menunjukkan adanya respon positif dari mahasiswa, dengan peningkatan keterlibatan aktif, kemampuan berpikir kritis, dan hasil belajar yang signifikan. Buku panduan ini juga membantu mahasiswa untuk lebih memahami konsep-konsep ilmiah dalam konteks kehidupan sehari-hari. Kesimpulannya, penerapan PJBL dengan fokus pada bahan pangan lokal NTT terbukti efektif dalam meningkatkan pemahaman dan keterampilan abad ke-21 mahasiswa.